Contrasting Seasonal Distribution Patterns of Two Boreal Aerial Hawking Bat Species in Finland - Piia Lundberg; Miika Kotila; Katarina Meramo; Kati M. Suominen; Miina Suutari; Tia‐Marie Pietikäinen; Ville Vasko; Thomas M. Lilley (Ecology and Evolution)
ABSTRACT Climate change poses significant consequences for temperate bat species, potentially altering their distribution ranges and generating novel interactions among species sharing similar ecological niches. Recent observations suggest distribution range expansion in the Palearctic aerial hawking bat, Pipistrellus nathusii, prompting an investigation into its interaction with Eptesicus nilssonii, a northern Palearctic species overlapping with the previous in many ecological characteristics. This study examines the spatiotemporal variations between the two boreal bat species to form an evidence‐based background onto which future research on, e.g., resource competition, can be built. A comprehensive community science project engaged over 470 participants from 45 high schools to collect acoustic data on bat echolocation calls across Finland, in northern Europe, during the summers of 2019–2020. Our modelling approach reveals distinct spatiotemporal patterns for each species. In early summer, E. nilssonii activity is concentrated in the southern region, whereas by late summer, observations are distributed across our study area, though predominantly in the south. This pattern suggests that E. nilssonii could exhibit post‐breeding vagrant behaviour, an observation only recently evidenced in bats. Conversely, the activity of P. nathusii remains notably low throughout the season, with observations concentrated along the south coast during both early and late seasons, making it challenging to fully model its distribution. Despite initial expectations of overlap given their similar foraging behaviour and habitat preferences, the limited activity and coastal association of P. nathusii suggest low competitive interaction with E. nilssonii. These findings contribute to our understanding of bat spatial ecology amid changing environmental conditions, emphasising the necessity for ongoing monitoring to ascertain the long‐term implications of shifting species distributions.